Comprehensive Education at University of Darussalam Gontor - Azmi Zarkasyi; Defi Firmansah; Dzkiri al Hafidz (Prodi Pendidikan Agama Islam, Fakultas Tarbiyah, Universitas Darussalam Gontor, 2022)
The view of education in Indonesia is still limited to a narrow concept, comprehensive education includes the three foundations for continuing the need of students, and comprehensive education is not limited to the development of the cognitive and professional aspects, comprehensive education is not limited to classroom education but includes education outside the classroom. Given the importance of comprehensive education and its development at Dar es Salaam University. The researcher saw to choose a topic and saw it under the title, Comprehensive Education at University of Darussalam Gontor.The purpose of this research: 1) to know the extent to which comprehensive education is implemented at University of Darussalam Gontor. 2) Knowledge of the supporting and discouraging factors of comprehensive education University of Darussalam Gontor. This research was a field research of the type of qualitative research (Descriptive Qualitative) the researcher used this type to obtain comprehensive education data at University of Darussalam Gontor. In order to obtain the data needed, the researcher took three approaches, the observational approach, the interview method, and the written documents. For data analysis, the researcher used the Mills and Hubertman approach, where it contains data reduction, data presentation and correlation, analysis of the collection of data collected in a note- and interview manner, written documents, and the authenticity of the data using triangulation.The result of this study can be concluded as follows: 1) The implementation of comprehensive education at University of Darussalam Gontor covers all aspects, and relates to four areas: male, intellectual, taste and sports, and these journals are associated with science, faith and work. 2) For the factors supporting comprehensive education at University of Darussalam Gontor due to the full facilities and environment funding i.e. scholarships and all academic support and student resources. The disincentives to comprehensive education at University of Darussalam Gontor lack facilities, interests and talents, and a decrease in student awareness, lectures and the environment.